On end to end network slicing for 5G communication systems. Issue 4 (23rd June 2016) - An, X.; Zhou, C.; Trivisonno, R.; Guerzoni, R.; Kaloxylos, A.; Soldani, D.; Hecker, A.
Abstract: The heterogeneity in use cases and the need to support diverse requirements from vertical markets are the main drivers for new design principles of 5G communication systems. In this paper, we review the notion of plastic architecture and propose an end to end network slicing concept to serve new 5G capabilities and features in a flexible and efficient manner. Besides the concept definition, we address in particular the key issue of how 5G devices may be enabled to discover, select and access the most appropriate E2E network slices. To solve the issue, we developed a novel Device Triggered Network Control mechanism and evaluated its performance and implementation cost with respect to alternative available schemes, where the slicing concept was applied only to the core network domain of the communication system. Simulation results showed two digits gains in terms of attachment delay and signalling overhead. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents an end‐to‐end network slicing concept as a key enabler for 5G system, allowing independent design and operation of tailored network architectures to support heterogeneous 5G use cases. The paper also addresses the key issue of enabling 5G devices to discover and access the most appropriate end‐to‐end network slices. A novel Device Triggered Network Control mechanism is proposed, evaluated and compared with alternative schemes, where the slicing concept applies to the core network only.